Adsorption of lead from aqueous solution using modified activated carbon prepared from palm kernel shell - Akaangee, Pam Aloysius (2018)
Motivated by adsorbent/liquid-interactive interfacial character, a major study within this thesis examines lead (Pb) adsorption on activated carbon. Pb was chosen as a model because it is abundant in aqueous waste, a potential risk factor for both human health and the environment and the focus of prior scientific investigation. Convectional techniques for Pb removal in aqueous solutions have inherited limitations and collateral effects. Adsorption onto solid adsorbent especially activated carbon, is an excellent strategy to eliminate Pb(II) from solution due to the high efficiency of adsorption and sorption capacity. On this front, activated carbon (AC) was prepared by chemical treatment of palm kernel shell (PKS) using H3PO4 and later modified using citric acid (CA) and ethylenediaminetetraacetic acid (EDTA). The respective physicochemical properties of the AC itself and the modified AC are identified using FTIR, FESEM, BET surface area and elemental analysis. The adsorption behavior of modified activated carbon is also put into context by calculations of interaction potentials through kinetics and isotherm models. Adsorption in batch method are benchmarked against adsorption in column studies, where the latter represents a real-world industrial situation and with potential for use in industries for water treatment. The activated carbon produced were mainly microporous in nature with BET surface area and pHpzc ranged from 548 m2/g to 1560 m2/g and 2 to 4.5, respectively. AC-600 2:1 exhibited the highest Pb(II) removal and was subjected to CA and EDTA modification. The adsorption process was endothermic and spontaneous in nature and the data fitted the pseudo-second order kinetics and Langmuir isotherm model. The maximum adsorption capacity of Pb(II) was in the sequence of AC-PKS (86.2 mg/g) < AC-CA (103.1 mg/g ) < AC-EDTA (104.2 mg/g), at 25 ± 1C and pH 5. Chemical reaction and mass transfer at the interface were the rate limiting steps during the adsorption of Pb(II). Both AC-CA and AC-EDTA showed good regeneration and reusability properties for Pb(II) adsorption. The result of the competitive adsorption studies, involving Pb(II), Cu(II) and Zn(II) showed strong antagonism in the multi-ions adsorption with the adsorbents showing more affinity towards Pb(II). The modified activated carbons also showed better adsorption performance in removing Pb(II) from electroplating wastewater than from the river water sample. In the fixed-bed column studies, both the flow rate and bed height influenced the column performance; increase in flow rate resulted in early breakthrough and exhaustion time, though with less adsorption of Pb(II). On the other hand, increased bed height leads to extended exhaustion time with improved column performance. Thomas and Yoon-Nelson models successfully modeled the breakthrough curve for dynamic adsorption of Pb(II) on the modified activated carbon. In conclusion, the adsorbents can adsorbed Pb(II) in both batch and column studies. The modified ACs exhibited higher adsorption capacities due to OH, COOH, and NH complexation with the metal ions. The performance of these adsorbents, benchmarked against other low cost adsorbents, is promising. These findings illustrate that the metal ion adsorption at the ionic scale in aqueous environment is through ion exchange, π-π interactions or complexation reaction.